Implementasi Aplikasi SI-MASTER Dalam Meningkatkan Efektivitas Administrasi Kepegawaian Pada Badan Kepegawaian Daerah Provinsi Jawa Timur - Irmayanti, Eka Wahyu Toriq; Handoko, V. Rudy; Indartuti, Endang (Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to accelerating and simplifying the civil service administration process, the application is expected to improve efficiency and transparency in the management of employee data, including applications for promotions, transfers, and promotions. This research uses a qualitative method with a case study approach, involving interviews with employees and application managers to collect data on their perceptions and experiences in using SI-MASTER. Overall, this study concludes that the SI-MASTER application contributes positively to the effectiveness of personnel administration, but still requires improvement in several aspects to reach its full potential. This thesis is expected to provide insights for policy makers and practitioners in managing a more efficient and responsive personnel administration.